Crosswind Monitoring And Detection System At Highway With IoT Features - Saat, Shahrizal; Zakaria, Nur Shahirah; Mohd Tumari, Mohd Zaidi; Hussin, Mohamed Saiful Firdaus; Muhammad Mustafa, Ahmad Nizamuddin; Adip, Mohd Anuar (Medwell Journals, 2019)
The term crosswinds are mean the horizontal winds blowing at 90° from the direction of travels with the speed of 12.5 miles/sec. Crosswind could make a trouble when traveling on wet or slippery roads, especially, during heavy rain and thunderstorms. It can make the vehicle overturning when crosswind blows through it. Windsock invisible at night can cause danger to highway users. This problem can increase the risk of being involved in the accident. To overcome this problem, the crosswind detection for direction and speed monitoring system at highway is being introduced. The signal from speed and direction sensor will be processed by controller and transmitted to the cloud. The outputs from the controller will be transmitted to the LCD screen to display the current information of crosswind and give the warning to the road users. LED light will indicate the status of the crosswind. Controller will update the data to the cloud through WiFi module. Data stored in the cloud can be accessed by user using Blynk App. It could help to reduce potential of accident occur, especially, at night for highway user.